Epidemiological Study of Anti-HPV16/18 Seropositivity and Subsequent Risk of HPV16 and -18 Infections - Safaeian, Mahboobeh (Oxford University Press, 2010)
BACKGROUND: Infection with human papillomavirus (HPV) 16 or HPV18 elicits an antibody response, but whether the elicited antibodies protect women against subsequent infection by a homologous HPV type compared with seronegative women is unknown. METHODS: Study participants were women aged 18–25 years at enrollment in the control group of the ongoing National Cancer Institute–sponsored, community-based, randomized HPV16/18 Costa Rica Vaccine Trial. At enrollment, 2813 participants were negative for cervical HPV16 DNA and 2950 for HPV18 DNA. Women were interviewed regarding sociodemographic data and medical and health history. Medical and pelvic examinations were conducted for all consenting sexually experienced women. Serum samples taken at enrollment were tested for total HPV16/18 antibodies with a polyclonal enzyme-linked immunosorbent assay, and cervical specimens were tested for type-specific HPV DNA over 4 years of follow-up. Using Poisson regression, we compared rate ratios of newly detected cervical HPV16 or HPV18 infection among homologous HPV-seropositive and HPV-seronegative women, adjusting for age, education, marital status, lifetime number of sexual partners, and smoking. RESULTS: There were 231 newly detected HPV16 infections during 5886 person-years among HPV16-seronegative women compared with 12 newly detected HPV16 infections during 581 person-years among HPV16-seropositive women with the highest HPV16 sero-levels. There were 136 newly detected HPV18 infections during 6352 person-years among HPV18-seronegative women compared with six new infections detected during 675 person-years among HPV18 seropositives with the highest sero-levels. After controlling for risk factors associated with newly detected HPV infection, having high HPV16 antibody titer at enrollment was associated with a reduced risk of subsequent HPV16 infection (women in the highest tertile of HPV16 antibody titers, adjusted rate ratio = 0.50, 95% confidence interval = 0.26 to 0.86 vs HPV16-seronegative women). Similarly, having high HPV18 antibody titer at enrollment was associated with a reduced risk of subsequent HPV18 infection (women in the highest tertile of HPV18 antibody titers, adjusted rate ratio = 0.36, 95% confidence interval = 0.14 to 0.76 vs HPV18-seronegative women). CONCLUSION: In this study population, having high antibody levels against HPV16 and HPV18 following natural infection was associated with reduced risk of subsequent HPV16 and HPV18 infections.